Evaluation of the maturation of Swiss-type cheese in a prototype system of NIR spectroscopy and artificial intelligence. - Oblitas Cruz, Jimy Frank; Cieza Rimarachín, Yuleyci; Cruz Oblitas, José André (LACCEI, 2025)
This proposal aims to evaluate the efficiency of classification and determination of the maturation conditions of Swiss-type cheese through a prototype system using NIR spectroscopy and artificial intelligence. The goal is to create an economical and scalable system to improve the production capabilities of cheese companies. The work is divided into three phases: (a) the development of logical sequences for classification and quality determination; (b) the development of the prototype system at the hardware and software level that will allow data collection in a cheese company, obtain NIR profiles, and control actuators in a classification system; and (c) the comparison of results and classification. The construction and operation of the portable NIR system for cheese maturation evaluation were achieved. It was observed that classifying the cheeses based on maturation days is feasible, with the most determining wavelength found between 1000 nm and 1450 nm, which is related to the presence of fatty acids in the samples. Therefore, low-cost equipment like the one designed and built can be used in industry, and since this technology does not require a complex sample process, it can be widely used in the cheese industry.